2012
DOI: 10.1158/1078-0432.ccr-11-2272
|View full text |Cite
|
Sign up to set email alerts
|

Association of HER2/ErbB2 Expression and Gene Amplification with Pathologic Features and Prognosis in Esophageal Adenocarcinomas

Abstract: Purpose We examined the frequency, tumor characteristics, and prognostic impact of HER2 protein expression and gene amplification in patients with curatively resected esophageal adenocarcinoma (EAC). Experimental Design HER2 expression was analyzed by immunohistochemistry (IHC) in surgical EAC specimens (n=713). Gene amplification was examined by fluorescence in situ hybridization (FISH) in a large subset (n=344). Most tumors were T3–4 (66%) or node-positive (72%); 95% were located in the esophagus or gastro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 47 publications
15
104
1
Order By: Relevance
“…The relevant prognostic value attributed to tumor location in the current study is consistent with previous reports suggesting worse outcomes for junctional primaries [2,23] and should rule out the superiority of adjuvant chemotherapy over perioperative chemotherapy. Our findings are in substantial agreement with those reported by Yoon et al, suggesting a strong association between HER2 positivity and better survival outcomes in patients with esophageal adenocarcinoma [24]. Also, improved survival for patients with HER2 overexpression was hypothesized in the frame of the ToGA study [20].…”
Section: Discussionsupporting
confidence: 93%
“…The relevant prognostic value attributed to tumor location in the current study is consistent with previous reports suggesting worse outcomes for junctional primaries [2,23] and should rule out the superiority of adjuvant chemotherapy over perioperative chemotherapy. Our findings are in substantial agreement with those reported by Yoon et al, suggesting a strong association between HER2 positivity and better survival outcomes in patients with esophageal adenocarcinoma [24]. Also, improved survival for patients with HER2 overexpression was hypothesized in the frame of the ToGA study [20].…”
Section: Discussionsupporting
confidence: 93%
“…However, the frequency of HER2 amplification was found to be significantly higher (p=0.004) in moderately differentiated tumors (13/22) compared with poor or well differentiated tumors (1/6 and 7/61 respectively). Yoon [69](2012) study supported our finding that HER2 amplification cases were significantly associated with better differentiation, but HER2 amplification cases were not associated with age and gender. However, they also showed that HER2 amplification was associated with lower depth of tumor invasion (T stage), fewer malignant nodes, and absence of signet ring cells.…”
Section: Her2 Amplification or Overexpression Correlating With Patienmentioning
confidence: 58%
“…The reported rate of HER2 gene amplification vary from 6.5% -30% (4,24,25). In a study performed by Wu et al HER2/neu overexpression was 14.1% in patients with ESCC (26). In contrast, HER2 positivity in a study developed by Gonzaga et al (18) was 21% in ESCC patients.…”
Section: Discussionmentioning
confidence: 96%